Japan's Lost Decade : Policies for Economic Revival - Callen, Tim.; Ostry, Jonathan (Washington, D.C. : International Monetary Fund, 2003)
Japan's weak economic performance in the 1990s has had implications not only for its own people, but for the world economy more generally, given Japan's importance as a trading partner and supplier of capital. Therefore, it is essential that Japan unlock its growth potential. The IMF has worked with the Japanese authorities to identify the policies needed to bring Japan's economy out of its recent slump. This book contributes to this ongoing debate, whose major topics include the need for an integrated policy strategy based on the decisive restructuring of the banking and corporate sectors, combined with macroeconomic policies designed to bring an end to deflation.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet